Kompetenzen für eine Nachhaltige Entwicklung aus der Perspektive beruflicher Praxis Eine empirische Untersuchung zu idealtypischen subjektiven Theorien über nachhaltigkeitsbezogene Anforderungen - Ruesch Schweizer, Corinne (Schriftenreihe "Ökologie und Erziehungswissenschaft" der Kommission Bildung für nachhaltige Entwicklung der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2023)
University graduates face a multitude of challenges after graduation - including sustainability-related requirements in professional practice. But what should sustainability competence enable them to do in professional practice? What is the role of higher education institutions in the provision of sustainability-related study programmes? Corinne Ruesch Schweizer explores these questions, which are mostly discussed in normative terms, in a qualitative-empirical study and thus not only provides a sound basis for curricular decisions and reflections in higher education for sustainable development, but also makes a long-demanded specification of the concept of sustainability competence.